Strengthening Harmony in The Midst of The Rapid Advancement of Information Technology - Siroj, Akhmad Munib (Institut Studi Islam Muhammadiyah Pacitan, 2025)
Indonesia is a pluralistic country in many aspects, including race, ethnicity, regional languages, customs, and religion. To manage this diversity in terms of ethnicity, religion, race, and intergroup relations (SARA), the government frames it within the format of religious harmony, which is defined as